Method for evaluating graphitization degree of coal-series graphite

Through a multi-step comprehensive evaluation method, combined with multiple testing methods and data analysis, the problem of difficulty in accurately judging the degree of graphitization of coal-based graphitization in the existing technology is solved, and a comprehensive and accurate evaluation of the degree of graphitization of coal-based graphitization is achieved, and the credibility of the evaluation results is improved.

CN119534073AInactive Publication Date: 2025-02-28CHINA UNIV OF MINING & TECH

Patent Information

Application Number
CN202411731020.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

It is difficult to accurately judge the degree of graphitization of coal-based graphite because the degree of graphitization is a continuous gradual process and lacks stage-by-stage distinction points.

Method used

A multi-step comprehensive evaluation method is adopted, including sample preparation, a variety of testing methods (such as X-ray diffraction, laser Raman spectroscopy, optical experiments, scanning electron microscopy, transmission electron microscopy, etc.) and comprehensive weight calculation, and the graphitization degree evaluation model is constructed to determine the graphitization degree of the sample.

Benefits of technology

Through a variety of testing methods and data analysis, the degree of graphitization of coal-based graphite is comprehensively and accurately evaluated, avoid misjudgment caused by a single discriminant parameter, improve the credibility of evaluation results, and provide an open evaluation index system to adapt to different research purposes and application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119534073A_ABST
    Figure CN119534073A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of graphitization degree detection, and particularly relates to a method for evaluating the graphitization degree of coal-series graphite, which comprises the following steps: step 1, treating a coal-series graphite sample to prepare sample forms meeting different test requirements, step 2, analyzing the sample to obtain data characteristics, and calculating the graphitization degree of the coal-series graphite according to the data characteristics. The method comprises the following steps of 1, obtaining a sample, 2, obtaining a sample, 3, obtaining evaluation indexes and structural characteristics of the sample, 4, constructing a sample graphitization degree evaluation model, and 5, comparing the sample characteristics with the graphitization model to determine the graphitization degree of the sample. According to the method, the sample graphitization degree dynamic evaluation model is established based on the sample data, evaluation requirements of various graphitization degrees can be well compatible, the method is not only suitable for various sample data types and characteristics, but also meets various evaluation precision requirements, and particularly, the method can be directly utilized when graphitization grades need to be subdivided; other changes and more calculation steps do not need to be made.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of graphitization degree detection, and in particular relates to a method for evaluating the graphitization degree of coal-based graphite. Background Art

[0002] Coal-based graphite is the product of coal entering the graphitization stage after undergoing magmatic thermal metamorphism and tectonic stress. It develops graphite structures to varying degrees, has the physical and chemical characteristics and process properties of graphite or graphite-like materials, and is an important supplement to strategic mineral crystalline graphite. Coal-based graphite is an aggregate of graphitized components of varying degrees of evolution and residual coal rock microscopic components. It has the dual attributes of mineralogy and petrology or ore science. It is different from crystalline flake graphite minerals of regional metamorphic origin. Conventional methods are difficult to distinguish between coal-based graphite and highly metamorphic anthracite, and the two are often confused.

[0003] The current method for identifying coal-based graphite is mainly laboratory measurement. In the laboratory, observe whether the color of the sample has a metallic luster and whether the texture is fine and dirty. Then, combine the industrial analysis of coal to detect the fixed carbon content in the sample, and use the microphotometer method to obtain the maximum reflectivity of the vitrinite to determine the degree of deterioration of the sample. At the same time, combine a series of laboratory methods such as X-ray diffraction technology (XRD) and laser Raman spectroscopy technology to determine whether the sample is coal-based graphite. However, the comprehensive efficiency of these methods can generally only determine whether the sample is coal-based graphite, and there are contradictions in the judgment criteria of different test methods. The degree of graphitization of coal-based graphite is a continuous gradual process, and there is no stage-by-stage distinction point. It is difficult to judge the degree of graphitization of coal-based graphite by traditional means.

[0004] A Chinese patent with patent announcement number CN115876817A discloses a method for testing the degree of graphitization, comprising the following steps: S1, obtaining XRD diffraction data of graphite materials; S2, obtaining the crystal structure file of standard graphite in the crystal structure database; S3, importing the XRD diffraction data and the crystal structure file into the data refinement software, and refining the crystal structure data to obtain the values ​​of the unit cell parameters; S4, substituting the unit cell parameters into the graphitization degree calculation formula to obtain the graphitization degree of the graphite material. The above invention can only determine whether the sample is coal-based graphite, and the graphitization degree of coal-based graphite is a continuous gradual process, and there is no stage-by-stage distinction point. Therefore, it is difficult for the above invention to judge the graphitization degree of coal-based graphite. Summary of the invention

[0005] The technical problem to be solved by the present invention is that in the above-mentioned prior art, it is only possible to determine whether the sample is coal-based graphite, and the degree of graphitization of coal-based graphite is a continuous gradual process without any stage-by-stage distinction points, making it difficult to judge the degree of graphitization of coal-based graphite.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0007] A method for evaluating the graphitization degree of coal-based graphite comprises the following steps:

[0008] Step 1: Process the coal-based graphite sample to prepare a sample form suitable for different testing requirements;

[0009] Step 2: Analyze the sample to obtain data features;

[0010] Step 3: Obtain evaluation indicators and structural characteristics of the sample;

[0011] Step 4: Construct a graphitization degree evaluation model for the samples;

[0012] Step 5: Compare the sample characteristics with the graphitization model to determine the degree of graphitization of the sample.

[0013] By adopting the above technical scheme, multiple testing methods and data analysis, the degree of graphitization of coal-based graphite can be comprehensively and accurately evaluated, avoiding misjudgment caused by a single discrimination parameter. Combined with microstructure analysis and macroscopic property testing, it can more accurately reflect the true situation of the sample, use objective data and scientific methods to reduce the influence of subjective factors, and improve the credibility of the evaluation results. An open evaluation index system is provided, which can be adjusted according to actual needs to adapt to different research purposes and application scenarios.

[0014] Further, in step 1, the collected coal-based graphite samples are prepared, including coal brick slices and ultrafine powder samples; wherein, the coal brick slices are used for optical experiments, and the size of the coal bricks is prepared into a round cake with a diameter of 20mm-30mm and a thickness of 2-3mm. The surface of the coal bricks is gradually polished using sandpaper of different particle sizes, firstly using coarse sandpaper to remove the uneven parts of the surface of the coal bricks, and then fine sandpaper is used for fine polishing until the surface is smooth, and the polished surface of the coal bricks is then polished to eliminate scratches, and diamond polishing paste or special polishing liquid is used in combination with a polishing cloth for polishing until the surface reaches a mirror effect, and after grinding and polishing, the surface of the coal bricks is thoroughly cleaned with distilled water or deionized water to ensure that there is no residual abrasive or polishing agent, and then dried naturally or blown dry with a hair dryer;

[0015] Among them, ultrafine powder samples are used for X-ray diffraction and laser Raman spectroscopy experimental tests to obtain graphite carbon layer reticular diffraction peak data and Raman spectral parameters. The samples need to be ground to a particle size not exceeding 42μm to ensure the uniformity and representativeness of the samples. Planetary ball mills or vibration mills are used for grinding. During the grinding process, samples should be taken regularly to check the particle size to ensure that the requirements are met. After grinding, the samples are screened using a standard sieve to ensure that the particle size of all samples is less than 42μm.

[0016] By adopting the above technical solution, the powder is ground to a particle size of less than 42μm, ensuring the uniformity and representativeness of the sample, which is beneficial to the accuracy and reliability of X-ray diffraction and laser Raman spectroscopy experiments. Screening ensures that the particle size of all samples is less than 42μm, avoiding the interference of large particles on the experimental results. The samples are stored in dry and clean containers to avoid moisture absorption or contamination, ensuring the purity and stability of the samples. The uniformity and representativeness of the ultrafine powder samples improve the accuracy and reliability of the experimental data, which helps to more accurately evaluate the degree of graphitization of coal-based graphite.

[0017] Furthermore, in step 2, specifically:

[0018] Step 21: Place the sample in a muffle furnace preheated to 900±10°C for 7 minutes, take out the sample, cool it to room temperature, weigh it, and calculate the volatile matter yield:

[0019]

[0020] Among them, V daf represents the volatile matter yield, m1 represents the weight of the sample before volatilization, and m2 represents the weight of the sample after volatilization;

[0021] Step 22: Place the sample in a muffle furnace, gradually raise the temperature to 815±10°C, maintain for 2 hours, take out the sample, cool it to room temperature, weigh it, and calculate the ash yield:

[0022]

[0023] Among them, m3 represents the ash weight, A d represents the ash yield;

[0024] Step 23: Calculate the fixed carbon content of the sample based on the above volatile matter yield and ash yield,

[0025] F cd =100-(V daf +A d +M ad );

[0026] Among them, M ad is the standard moisture content, F cd is the fixed carbon content.

[0027] By adopting the above technical scheme, the volatile matter yield, ash yield and fixed carbon content are determined, so that the chemical composition and physical properties of coal-based graphite samples can be fully understood. The experiment is carried out strictly in accordance with the standard method to ensure the accuracy and reliability of the data. The determination of volatile matter yield and ash yield provides important basic data for the subsequent evaluation of the degree of graphitization. With reference to national standards, the standardization and consistency of the experimental methods are ensured, which is convenient for comparison with other research results. By accurately weighing and controlling the experimental conditions, the representativeness of the samples is ensured and experimental errors are avoided. The calculation of fixed carbon content combines the volatile matter yield and ash yield, provides complete sample chemical composition information, and helps to more comprehensively evaluate the degree of graphitization of coal-based graphite.

[0028] Furthermore, in step 3, specifically:

[0029] Step 31: Use an element analyzer to analyze the sample to obtain the content of carbon and hydrogen elements;

[0030] Step 32: Use a radiation source to irradiate the sample, obtain the graphite carbon layer diffraction peak data, and use the Bragg formula to calculate the aromatic layer spacing value d 002 :

[0031]

[0032] Among them, θ represents the angle corresponding to the half-width of the diffraction peak, and λ represents the wavelength of the radiation source.

[0033] Step 33: Use a 532nm or 633nm laser excitation source, select a suitable excitation time according to the fluorescence background and signal intensity of the sample, obtain the Raman spectrum parameters D1, D2 and the peak areas SD1, SD2 and SG of the G peak of the sample, and calculate the Raman spectrum discrimination index R2 using the peak area:

[0034]

[0035] Step 34: Observe the microstructure of the sample, record the microscopic component composition characteristics of the sample, observe the deformation characteristics of the sample, take photos through a microscope, and record the optical indicators of the sample.

[0036] By adopting the above technical scheme, multiple testing methods (element analysis, XRD, Raman spectroscopy, optical experiments) can obtain multi-faceted information of the samples to ensure the comprehensiveness and accuracy of the evaluation. Each test method has clear standards and operating steps to ensure the accuracy and reliability of the data. For example, XRD and Raman spectroscopy can provide microstructure and chemical bond information, while elemental analysis and optical experiments provide macro and microstructural characteristics. With reference to national standards (such as GB / T 31391-2015, GB / T 212-2008, etc.), the standardization and consistency of the experimental methods are ensured, which is convenient for comparison with other research results. By accurately weighing and controlling the experimental conditions, the representativeness of the samples is ensured and experimental errors are avoided. The combination of various test methods provides complete information on the chemical composition and physical properties of the samples, which is helpful to more comprehensively evaluate the degree of graphitization of coal-based graphite.

[0037] Further, in which, the pre-graphitization stage, m=1; the primary graphitization stage, m=2; the intermediate graphitization stage, m=3; the high graphitization stage, m=4; the sample level to be evaluated, m=5;

[0038] The evaluation standard data matrix A of sample grade membership is constructed based on the coal-based graphitization grade m-1 ij , A ij (ai1,ai2,ai3,…aij);

[0039] Where i is the evaluation level membership, i = 1, 2, 3, ... h-1), j is the number of evaluation indicators, j = 1, 2, 3 ... n, and the maximum value of n is 12;

[0040] Establish evaluation index matrix A kj , A kj =(ak1, ak2, ak3 ... akn);

[0041] The evaluation index standard matrix A mj And the evaluation object data matrix A ij Jointly establish a comprehensive evaluation matrix B ij

[0042] B ij =(b ij )m×n, where i=1, 2, 3, …m and j=1, 2, 3 …n.

[0043] By adopting the above technical scheme and comprehensive consideration of multiple evaluation indicators, the degree of graphitization of coal-based graphite can be comprehensively evaluated, avoiding the limitations of a single indicator. The constructed evaluation standard data matrix and evaluation indicator matrix ensure the accuracy and reliability of the data, which is helpful to more accurately evaluate the degree of graphitization of the sample. The construction of the evaluation standard data matrix and the evaluation indicator matrix follows certain standards and specifications to ensure the scientificity and consistency of the evaluation method. The evaluation indicator matrix can be adjusted according to actual needs, increasing or decreasing evaluation indicators to adapt to different research purposes and application scenarios. Through the comprehensive evaluation matrix, multiple experimental data can be systematically integrated to provide complete sample characteristic information, which is helpful to more comprehensively understand the properties of the sample. The comprehensive evaluation matrix provides important basic data for subsequent graphitization degree evaluation and helps to formulate reasonable production and scientific research strategies.

[0044] Furthermore, the comprehensive evaluation matrix B ij Normalize and get the normalized matrix X of the comprehensive evaluation matrix = (x ij )m×n, where the benefit-based evaluation index is normalized using the following formula:

[0045]

[0046] Cost-based indicators are normalized using the following formula:

[0047]

[0048] The linear ratio conversion method is used to standardize the comprehensive evaluation index matrix X, and the standardized matrix Y = (y ij )m×n, the calculation formula is:

[0049]

[0050] By adopting the above technical solutions, normalization and standardization processing make the data of different indicators comparable, avoiding errors caused by different dimensions, ensuring the accuracy and reliability of the data, and helping to more accurately evaluate the degree of graphitization of the samples. The normalization and standardization processing of the evaluation standard data matrix and the evaluation indicator matrix follows unified standards and methods, ensuring the scientificity and consistency of the evaluation method. The normalization and standardization processing methods can be adjusted according to actual needs to adapt to different research purposes and application scenarios. Through normalization and standardization processing, multiple experimental data can be systematically integrated to provide complete sample characteristic information, which helps to more comprehensively understand the nature of the samples. The data after normalization and standardization processing provides important basic data for subsequent graphitization degree evaluation and helps to formulate reasonable production and scientific research strategies.

[0051] Further, in step 5, the entropy value of the index information is calculated to determine the objective weight C of each index for evaluating the graphitization degree of coal-based graphite. j , the information entropy calculation method of the indicator is as follows:

[0052]

[0053] Among them, when y ij =0, then define limy ij →0y ij lm ij =0;

[0054]

[0055] Combined with the actual situation of each evaluation index, the subjective weight D of evaluating the graphitization degree of coal-based graphite is determined by using the hierarchical analysis method. j , establish the comprehensive weight matrix F of the evaluation index j , the calculation method of comprehensive weight is as follows:

[0056] F j =C j ×D j ;

[0057] Normalize the comprehensive weight of each indicator to obtain the evaluation weight coefficient ω of each indicator ij :

[0058]

[0059] By adopting the above technical solution, the entropy method is used to determine the objective weights, and the hierarchical analysis method is used to determine the subjective weights. This allows the evaluation results to take into account the objectivity of the data itself and incorporate the experience and judgment of experts, thereby improving the scientificity and rationality of the evaluation. The entropy method normalizes and standardizes the data to make the data of different indicators comparable, thus avoiding errors caused by different dimensions. The calculation method of the comprehensive weight ensures the accuracy and reliability of the data, which helps to more accurately evaluate the degree of graphitization of the samples. The consistency test of the hierarchical analysis method ensures the rationality of the judgment matrix and avoids the arbitrariness of subjective judgment. The weights of the evaluation indicators can be adjusted according to actual needs to adapt to different research purposes and application scenarios.

[0060] Furthermore, the graphitization degree of the sample is comprehensively evaluated and the graphitization coefficient GR of the sample is calculated:

[0061]

[0062] Comparative analysis of the graphitization coefficient GR of the samples m and GR p , GRi , GR q , GR h The size of the sample determines the degree of graphitization.

[0063] The present invention has the following beneficial effects:

[0064] 1. The present invention determines the objective weights by the entropy method and the subjective weights by the analytic hierarchy process (AHP), and finally establishes a comprehensive weight matrix, which combines the objectivity of the data and the subjectivity of the expert experience, and ensures the scientificity and rationality of the evaluation results. The entropy method normalizes and standardizes the data to make the data of different indicators comparable, avoiding the errors caused by different dimensions. The analytic hierarchy process ensures the rationality of the judgment matrix through consistency testing, and avoids the arbitrariness of subjective judgment.

[0065] 2. The present invention provides a method for comprehensively evaluating the graphitization degree of coal-based graphite. Through a multi-step comprehensive evaluation, including sample preparation, multiple testing methods (such as X-ray diffraction, laser Raman spectroscopy, optical experiments, scanning electron microscopy, transmission electron microscopy, etc.) and calculation of comprehensive weights, the graphitization degree of coal-based graphite can be comprehensively and accurately evaluated, avoiding the limitation of a single indicator;

[0066] 3. The present invention can comprehensively and accurately evaluate the degree of graphitization of coal-based graphite through a multi-step comprehensive evaluation method, including sample preparation, multiple testing methods (such as X-ray diffraction, laser Raman spectroscopy, optical experiments, scanning electron microscopy, transmission electron microscopy, etc.) and calculation of comprehensive weights. It not only covers macroscopic and microscopic characteristics, but also combines various information on chemical composition and physical structure, ensuring the comprehensiveness and accuracy of the evaluation results. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION

[0068] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific preferred embodiments.

[0069] In the description of the present invention, it should be understood that the terms "left side", "right side", "upper part", "lower part" and the like indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. "First", "second" and the like do not indicate the importance of the components, and therefore cannot be understood as limiting the present invention. The specific dimensions used in this embodiment are only for illustrating the technical solution, and do not limit the scope of protection of the present invention.

[0070] like Figure 1 As shown, a method for evaluating the graphitization degree of coal-based graphite, the main calculation steps of the present invention are as follows:

[0071] 1. Prepare the collected coal-based graphite samples, including coal bricks for optical experiments. Prepare ultrafine coal powder (<42μm) for XRD and laser Raman spectroscopy experimental testing, and prepare the collected coal-based graphite samples, including coal brick slices and ultrafine powder samples; among them, coal brick slices are used for optical experiments, and the size of the coal brick is prepared into a round cake with a diameter of 25mm and a thickness of 2.5mm. Use sandpaper of different particle sizes to gradually grind the surface of the coal brick. First, use coarse sandpaper to remove the uneven parts of the surface of the coal brick, and then use fine sandpaper for fine grinding until the surface is smooth. The polished surface of the coal brick is then polished to eliminate scratches. Use diamond polishing paste or special polishing liquid with polishing cloth to polish until the surface reaches a mirror effect. After grinding and polishing, use distilled water or deionized water to thoroughly clean the surface of the coal brick to ensure that there is no residual abrasive or polishing agent, and then dry it naturally or with a hair dryer;

[0072] 2. Use GB / T212-2008 to conduct industrial analysis of coal on the prepared experimental samples to obtain the fixed carbon content F of the samples. cd and volatile matter yield (V daf ) data, put the sample into a muffle furnace preheated to 900℃, keep it for 7 minutes, take out the sample, cool it to room temperature, weigh it, and calculate the volatile matter yield:

[0073]

[0074] Among them, V daf represents the volatile matter yield, m1 represents the weight of the sample before volatilization, and m2 represents the weight of the sample after volatilization;

[0075] Step 22: Place the sample in a muffle furnace, gradually raise the temperature to 815°C, maintain for 2 hours, take out the sample, cool it to room temperature, weigh it, and calculate the ash yield:

[0076]

[0077] Among them, m3 represents the ash weight, A d represents the ash yield;

[0078] Step 23: Calculate the fixed carbon content of the sample based on the above volatile matter yield and ash yield,

[0079] F cd =100-(V daf +A d +M ad );

[0080] Among them, M ad is the standard moisture content, F cd is the fixed carbon content;

[0081] 3. Use GB / T 31391-2015 to perform elemental analysis on the prepared experimental samples, obtain the C and H element contents of the samples, and calculate the hydrogen-carbon atomic ratio C / H of the samples;

[0082] 4. The sample was crushed into powder with a particle size of less than 42 μm, and an XRD diffraction experiment was performed to obtain the graphite carbon layer network (002) and diffraction peak data. The aromatic layer spacing value d was calculated according to the Bragg formula. 002 , step 41: using an element analyzer to analyze the sample to obtain the content of carbon and hydrogen elements;

[0083] Step 42: Use a radiation source to irradiate the sample, obtain the graphite carbon layer diffraction peak data, and use the Bragg formula to calculate the aromatic layer spacing value d 002 :

[0084]

[0085] Among them, θ represents the angle corresponding to the half-width of the diffraction peak, and λ represents the wavelength of the radiation source.

[0086] Step 43: Use a 532nm or 633nm laser excitation source, select a suitable excitation time according to the fluorescence background and signal intensity of the sample, obtain the Raman spectrum parameters D1, D2 and the peak areas SD1, SD2 and SG of the G peak of the sample, and calculate the Raman spectrum discrimination index R2 using the peak area:

[0087]

[0088] Step 44: observe the microstructure of the sample, record the microscopic component composition characteristics of the sample, observe the deformation characteristics of the sample, take photos through a microscope, and record the optical indicators of the sample;

[0089] 5. Perform laser Raman test on the sample at the same time to obtain the Raman spectrum parameters of the sample, the peak areas SD1, SD2, and SG of the D1, D2, and G peaks. The Raman spectrum discrimination index R2 is calculated using the position of each main peak. The calculation formula of R2 is as follows:

[0090]

[0091] 6. Use the prepared coal bricks to conduct optical experimental judgment of the coal bricks, observe the microscopic components and deformation characteristics of the coal rock, and obtain the optical index Mc of coal-based graphite.

[0092] 7. Conduct a scanning electron microscope (SEM) experiment on coal samples to analyze the composition of minerals in the coal at a microscopic scale, analyze the particle size and shape of graphite particles, and combine the electron energy spectrum (EDS) experiment to identify specific elements in the coal. The two are combined to obtain the SEM index of coal-based graphite. According to the flake diameter, crystal morphology and degree of perfection, the degree of graphitization can be qualitatively determined, and the SEM index SE of coal-based graphite can be determined;

[0093] 8. Use high-resolution transmission electron microscopy (HRTEM) to obtain nanoscale coal-based graphite indicators, observe the shape and arrangement characteristics of the macromolecular structure at the nanoscale, and obtain the high-resolution indicator Hr of coal-based graphite;

[0094] 9. Based on GB / T 23561.2-2009, the true density and porosity of the sample are obtained experimentally as the density determination index DE and the porosity determination index Φ of coal-based graphite;

[0095] 10. Based on GB / T 1410-2006, the resistivity judgment index Rc of the coal-based graphite of the sample is obtained experimentally;

[0096] 11. In order to facilitate calculation, the graphitization degree of the sample to be evaluated is divided into four stages: pre-graphitization stage (GR p ), initial graphitization stage (GR i ), middle graphitization stage (GR m ), high graphitization stage (GR h ), these four stages constitute the criteria for judging the degree of graphitization of coal. The graphitization grade GRs of the sample to be evaluated. That is, the pre-graphitization stage, m = 1; the initial graphitization stage, m = 2; the middle graphitization stage, m = 3; the high graphitization stage, m = 4; the sample level to be evaluated, m = 5;

[0097] 12. Construct the evaluation standard matrix A of sample grade membership based on coal-based graphitization grade m-1 ij ,

[0098] A ij (a i1 ,a i2 ,a i3 ,…a ij ),

[0099] Among them, i is the evaluation level membership, i=1, 2, 3, ... m-1); j is the number of evaluation indicators, in the present invention, j=1, 2, 3...n, n is a maximum of 12.

[0100] 13. Establish the evaluation index matrix A based on the evaluation index object of the specific sample k , A kj =(a k1 ,ak2 ,a k3 …a kn ).

[0101] 14. Combine the evaluation index standard matrix and the evaluation object data matrix to establish a comprehensive evaluation matrix B ij

[0102] B ij =(b ij )m×n

[0103] Where i = 1, 2, 3, ... m, j = 1, 2, 3 ... n;

[0104] 15. Use the standardization method to convert the comprehensive evaluation matrix B ij Normalize and get the normalized matrix X of the comprehensive evaluation matrix = (x ij )m×n, where the benefit-based indicators are normalized using the following formula:

[0105]

[0106] Cost-based indicators are normalized using the following formula:

[0107]

[0108] The fixed carbon content F in the present invention cd Index, optical identification index M C , electron microscope energy spectrum index SE, transmission electron microscope index Hr, true density index DE are benefit indicators, and the rest are cost indicators.

[0109] 16. Use the linear ratio conversion method to standardize the comprehensive evaluation index matrix and obtain the standardized matrix Y = (y ij )m×n,

[0110]

[0111] 17. Calculate the entropy value of the index information to determine the objective weight of each index for evaluating the graphitization degree of coal. j .

[0112] The information entropy calculation method of each indicator is as follows:

[0113]

[0114] Among them, when y ij =0, then define limy ij →0y ij lm ij =0.

[0115]

[0116] 18. Combined with the actual situation of each evaluation index, the subjective weight D of evaluating the graphitization degree of coal is determined by using the hierarchical analysis method. j Subjective weight D j The specific data are shown in Table 1:

[0117]

[0118] Table 1

[0119] 19. Establish the comprehensive weight matrix F of evaluation indicators j ,The calculation method of comprehensive weight is as follows:

[0120] F j =C j ×D j

[0121] The comprehensive weights of each indicator are further normalized to obtain the evaluation weight coefficient ω of each indicator. j :

[0122]

[0123] 20. Comprehensively evaluate the graphitization degree of the sample and calculate the graphitization coefficient GR of the sample

[0124]

[0125] 21. Compare and analyze the graphitization degree of the sample, and compare and analyze the graphitization coefficient GRs and graphitization grade of the sample. Determine the graphitization degree of the sample. For example, when the evaluation result is:

[0126] GRP <GRs<GRi<GRm<GRh

[0127] This indicates that the degree of graphitization of the sample is between the pre-graphitization stage and the primary graphitization stage.

[0128] Through the above steps, the graphitization degree of the sample can be obtained, providing a certain engineering basis for the evaluation and mining of coal-based graphite.

[0129] The feasibility and applicability of the present invention are analyzed below by taking the actual data of a coal-based graphite mine in Fujian as an example:

[0130] For ease of understanding and calculation, all matrices in the present invention will be presented in table form, and specific information will be marked in the first row and column of the table.

[0131] 1. Obtain various index parameters for graphitization evaluation of coal-based graphite through experiments, as shown in Table 2;

[0132] 2. Construct the evaluation standard matrix A of sample grade membership based on coal-based graphitization grade m-1 ij ;

[0133]

[0134]

[0135] Table 2

[0136] 3. Establish the evaluation index matrix A based on the evaluation index object of the specific sample k ,Ak j =(a k1 ,a k2 ,a k3 …a kn ) The calculated graphitization degree is shown in Table 3:

[0137] <![CDATA[GR s ]]> 63 4 0.17 0.342 0.53 87 65 75 2.18 6 23

[0138] Table 3

[0139] 4. Combine the evaluation index standard matrix and the evaluation object data matrix to establish a comprehensive evaluation matrix B ij , the calculated graphitization degree is shown in Table 4:

[0140]

[0141] Table 4

[0142] 15. Use the standardization method to convert the comprehensive evaluation matrix B ij Normalize and get the normalized matrix X of the comprehensive evaluation matrix = (x ij )m×n, where the benefit index is normalized using the following formula, and the calculated graphitization degree is shown in Table 5:

[0143]

[0144] Table 5

[0145] 16. Use the linear ratio conversion method to standardize the comprehensive evaluation index matrix and obtain the standardized matrix Y = (y ij )m×n, the calculated graphitization degree is shown in Table 6:

[0146]

[0147] Table 6

[0148] 17. Calculate the entropy value of the index information to determine the objective weight of each index for evaluating the graphitization degree of coal. j, The calculated graphitization degree is shown in Table 7;

[0149] <![CDATA[E j ]]> 0.80 0.83 0.74 0.79 0.81 0.82 0.75 0.81 0.82 0.80 0.81

[0150] Table 7

[0151] After normalization, the data are shown in Table 8.

[0152] <![CDATA[C j ]]> 0.09 0.08 0.12 0.10 0.08 0.08 0.11 0.08 0.08 0.09 0.08

[0153] Table 8

[0154] 18. Combined with the actual conditions of each evaluation index, the subjective weight Dj for evaluating the graphitization degree of coal is determined by using the hierarchical analysis method. The specific data of the subjective weight Dj are shown in Table 9:

[0155]

[0156] Table 9

[0157] 19. Establish the comprehensive weight matrix F of evaluation indicators j , the calculation data of comprehensive weight is shown in Table 10:

[0158]

[0159]

[0160] Table 10

[0161] The comprehensive weights of each indicator are further normalized to obtain the evaluation weight coefficient ω of each indicator. j, The calculation results of each indicator are shown in Table 11:

[0162]

[0163] Table 11

[0164] 20. Comprehensively evaluate the graphitization degree of the samples and calculate the graphitization coefficient GR of the samples as shown in Table 12:

[0165] Graphitization grade GR <![CDATA[GR h ]]> 0.791424 <![CDATA[GR m ]]> 0.79128 <![CDATA[GR i ]]> 0.429336 <![CDATA[GR p ]]> 0.087713 <![CDATA[GR s ]]> 0.338795

[0166] Table 12

[0167] 21. Compare and analyze the graphitization degree of the samples and the graphitization coefficient GR of the samples s Determine the degree of graphitization of the sample. In this example,

[0168] GR p <GR s <GR i <GR m <GR h;

[0169] This indicates that the degree of graphitization of the sample is between the pre-graphitization stage and the primary graphitization stage.

[0170] The preferred embodiments of the present invention are described in detail above; however, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, various equivalent transformations can be made to the technical solutions of the present invention, and these equivalent transformations all belong to the protection scope of the present invention.

Claims

1. A method for evaluating the graphitization degree of coal-based graphite, characterized in that: The following steps are involved: Step 1: Process the coal-based graphite sample to prepare a sample form suitable for different testing requirements; Step 2: Analyze the sample to obtain data features; Step 3: Obtain evaluation indicators and structural characteristics of the sample; Step 4: Construct a graphitization degree evaluation model for the samples; Step 5: Compare the sample characteristics with the graphitization model to determine the degree of graphitization of the sample.

2. The method for evaluating the degree of graphitization of coal-based graphite according to claim 1, characterized in that: In step 1, the collected coal-based graphite samples are prepared, including coal brick slices and ultrafine powder samples; wherein, the coal brick slices are used for optical experiments, and the size of the coal bricks is prepared into a round cake with a diameter of 20mm-30mm and a thickness of 2-3mm. The surface of the coal bricks is gradually polished using sandpapers of different particle sizes, firstly using coarse sandpaper to remove the uneven parts of the surface of the coal bricks, and then fine sandpaper is used for fine polishing until the surface is smooth, and the polished surface of the coal bricks is then polished to eliminate scratches, and diamond polishing paste or special polishing liquid is used with a polishing cloth for polishing until the surface reaches a mirror effect. After grinding and polishing, the surface of the coal bricks is thoroughly cleaned with distilled water or deionized water to ensure that there is no residual abrasive or polishing agent, and then dried naturally or blown dry with a hair dryer; Among them, ultrafine powder samples are used for X-ray diffraction and laser Raman spectroscopy experimental tests to obtain graphite carbon layer reticular diffraction peak data and Raman spectral parameters. The samples need to be ground to a particle size not exceeding 42μm to ensure the uniformity and representativeness of the samples. Planetary ball mills or vibration mills are used for grinding. During the grinding process, samples should be taken regularly to check the particle size to ensure that the requirements are met. After grinding, the samples are screened using a standard sieve to ensure that the particle size of all samples is less than 42μm.

3. The method for evaluating the degree of graphitization of coal-based graphite according to claim 2, characterized in that: In step 2, specifically: Step 21: Place the sample in a muffle furnace preheated to 900±10°C for 7 minutes, take out the sample, cool it to room temperature, weigh it, and calculate the volatile matter yield: Among them, V daf represents the volatile matter yield, m1 represents the weight of the sample before volatilization, and m2 represents the weight of the sample after volatilization; Step 22: Place the sample in a muffle furnace, gradually raise the temperature to 815±10°C, maintain for 2 hours, take out the sample, cool it to room temperature, weigh it, and calculate the ash yield: Among them, m3 represents the ash weight, A d represents the ash yield; Step 23: Calculate the fixed carbon content of the sample based on the above volatile matter yield and ash yield, F cd =100-(V daf +A d +M ad ); Among them, M ad is the standard moisture content, F cd is the fixed carbon content.

4. The method for evaluating the degree of graphitization of coal-based graphite according to claim 1, characterized in that: In step 3, specifically: Step 31: Use an element analyzer to analyze the sample to obtain the content of carbon and hydrogen elements; Step 32: Use a radiation source to irradiate the sample, obtain the graphite carbon layer diffraction peak data, and use the Bragg formula to calculate the aromatic layer spacing value d 002 : Among them, θ represents the angle corresponding to the half-width of the diffraction peak, and λ represents the wavelength of the radiation source. Step 33: Use a 532nm or 633nm laser excitation source, select a suitable excitation time according to the fluorescence background and signal intensity of the sample, obtain the Raman spectrum parameters D1, D2 and the peak areas SD1, SD2 and SG of the G peak of the sample, and calculate the Raman spectrum discrimination index R2 using the peak area: Step 34: Observe the microstructure of the sample, record the microscopic component composition characteristics of the sample, observe the deformation characteristics of the sample, take photos through a microscope, and record the optical indicators of the sample.

5. The method for evaluating the degree of graphitization of coal-based graphite according to claim 1, characterized in that: In step 4, the graphitization degree of the sample to be evaluated is divided into the pre-graphitization stage, the primary graphitization stage, the middle graphitization stage and the high graphitization stage, which constitute the judgment standard of sample graphitization, among which the pre-graphitization stage is GR p , the initial graphitization stage is GR i , the graphitization stage is GR q , the high graphitization stage is GR h .

6. The method for evaluating the degree of graphitization of coal-based graphite according to claim 5, It is characterized in that Among them, pre-graphitization stage, m = 1; primary graphitization stage, m = 2; middle graphitization stage, m = 3; high graphitization stage, m = 4; sample level to be evaluated, m = 5; based on the coal-based graphitization level m-1, the evaluation standard data matrix A of sample level membership is constructed. ij , A ij (a i1 ,a i2 ,a i3 ,…a ij ); Where i is the evaluation level membership, i = 1, 2, 3, ... h-1), j is the number of evaluation indicators, j = 1, 2, 3 ... n, and the maximum value of n is 12; Establish evaluation index matrix A kj , A kj =(a k1 , a k2 , a k3 …a kn ); The evaluation index standard matrix A mj And the evaluation object data matrix A ij Jointly establish a comprehensive evaluation matrix B ij B ij =(b ij )m×n, where i=1, 2, 3, …m and j=1, 2, 3 …n.

7. The method for evaluating the degree of graphitization of coal-based graphite according to claim 6, characterized in that: The comprehensive evaluation matrix B ij Normalize and get the normalized matrix X of the comprehensive evaluation matrix = (x ij )m×n, where the benefit-based evaluation index is normalized using the following formula: Cost-based indicators are normalized using the following formula: The linear ratio conversion method is used to standardize the comprehensive evaluation index matrix X, and the standardized matrix Y = (y ij )m×n, the calculation formula is:

8. The method for evaluating the degree of graphitization of coal-based graphite according to claim 1, characterized in that: In step 5, the entropy value of the index information is calculated to determine the objective weight C of each index for evaluating the graphitization degree of coal-based graphite. j , the information entropy calculation method of the indicator is as follows: Among them, when y ij =0, then define limy ij →0y ij lm ij =0; Combined with the actual situation of each evaluation index, the subjective weight D of evaluating the graphitization degree of coal-based graphite is determined by using the hierarchical analysis method. j , establish the comprehensive weight matrix F of the evaluation index j , the calculation method of comprehensive weight is as follows: F j =C j ×D j ; Normalize the comprehensive weight of each indicator to obtain the evaluation weight coefficient ω of each indicator ij :

9. The method for evaluating the degree of graphitization of coal-based graphite according to claim 7, characterized in that: Comprehensively evaluate the graphitization degree of the sample and calculate the graphitization coefficient GR of the sample: Comparative analysis of the graphitization coefficient GR of the samples m and GR p , GR i , GR q , GR h The size of the sample determines the degree of graphitization.

Citation Information

Patent Citations

  • Graphitization degree testing method

    CN115876817A

  • Coal-series graphite mineral resource grading evaluation method

    CN112986539A

  • Comprehensive evaluation method for mud flat ecosystem

    CN116976694A

  • Comprehensive evaluation method for growth vigor of cotton

    CN117972449A

Cited By

  • Method and system for improving and optimizing graphitization process parameters of negative electrode material

    CN120509175A